Derivatives of grindelic acid: From a non-active natural diterpene to synthetic antitumor derivatives - Reta, Guillermo Federico (2013)
Using several reactions that include homologations and asymmetric epoxidations as well as Ugi and Huisgen couplings, we generated a small focused library of new derivatives from the labdane-type diterpene grindelic acid. These compounds were evaluated as cytotoxic agents against a panel of five human solid tumor cell lines (HBL-100, HeLa, SW1573, T-47D, and WiDr). The presence of the diamide functionalizations enhanced the cytotoxic effect. N-Benzyl-N-(1-(benzylamino)-2-methyl-1-oxopropan- 2-yl)grindelicamide, proved to be the most active product in all cell lines tested, with values of 0.95 (0.38) mM against HBL-100 cells.